1.2.5. Synthesis, crystal structure and catalytic activity of 2-methoxycarbonylethyldichlorotin hydroxide (Communications in Inorganic Synthesis, 2014)
Abstract: 2-methoxycarbonylethyldichlorotin hydroxide, CH3OCOCH2CH2SnCl2(OH) ( 1), has been synthesized by hydrolysis reaction and characterized by elemental analysis, FTIR, 1H NMR spectroscopy, and X-ray single crystal diffraction. CompoundÂ  1 is a centrosymmetric dimmer, and the tin atom approximates to octahedral geometry via an intramolecular carbonyl- to-tin coordination and hydroxo-bridging. The compound display high selectivity and good catalysis activity on the transesterification reaction of ethyl acetoacetate with an alcohol. Supporting information: FT-IR, 1H NMR, X-Ray, GC/MS analyses, Cif file.Â